Reduction of hepatitis B surface antigen in sequential versus add-on pegylated interferon to nucleoside/nucleotide analogue therapy in HBe-antigen-negative chronic hepatitis B patients: A pilot study. Issue 8 (November 2018) - Tatsukawa, Yumiko; Tsuge, Masataka; Kawakami, Yoshiiku; Hiyama, Yuichi; Murakami, Eisuke; Kurihara, Mio; Nomura, Motonobu; Tsushima, Ken; Uchida, Takuro; Nakahara, Takashi; Miki, Daiki; Kawaoka, Tomokazu; et al.
Background: Although pegylated interferon (PEG-IFN) and nucleotide/nucleoside analogue (NA) combination therapy is considered to be optimal for accelerating serum hepatitis B surface antigen (HBsAg) reduction, the effect is limited, and the best approach to PEG-IFN treatment for chronic hepatitis B patients during long-term NA therapy has yet to be determined. Methods: A total of 21 hepatitis B e antigen-negative chronic hepatitis B patients whose HBV DNA levels were suppressed to undetectable levels by NA therapy were administrated PEG-IFN-α2a for 48 weeks (sequential therapy: 10, add-on therapy: 11). Factors associated with HBsAg reduction by PEG-IFN therapy were analysed. Results: During PEG-IFN treatment, HBsAg levels were reduced by 0.48 log IU/ml. More than 1 log IU/ml of HBsAg reduction was observed in eight patients (sequential therapy: six, add-on therapy: two), and one patient with sequential therapy achieved HBsAg loss. By univariate analysis, sequential therapy was marginally associated with more than 1 log IU/ml HBsAg reduction during PEG-IFN treatment ( P =0.060). After PEG-IFN treatment, only five patients, including the patient with HBsAg loss, achieved more than 0.5 log IU/ml of HBsAg reduction by 1 year after PEG-IFN treatment. By univariate analysis, sequential therapy was significantly associated with HBsAg reduction after PEG-IFN treatment ( P =0.012). In addition, alanine aminotransferase elevation during PEG-IFN therapy and lower serum interleukin-8 level at the end of PEG-IFN treatment were also significantly associated with HBsAg reduction by 1 year after PEG-IFN treatment ( P =0.038, P =0.044, respectively). Conclusions: Sequential therapy may be superior to addon therapy in reducing HBsAg levels during long-term NA therapy in chronic hepatitis B patients.